The Significances of Maslahah Concept and Doctrine of Maqasid (Objectives) Al-Shari'ah in Project Evaluation - Abdullaah Jalil (Universiti Sains Islam Malaysia, 2012)
The concept of maslahah and doctrine of Maqasid (objectives) al-Shari'ah as put forward predominantly by Al-Ghazali and Al-Shatibi could be referred for developing choices and preferences from Islamic perspective. The two concepts shall have a great impact on the project evaluation procedure in an Islamic framework. The paper aims to analyze the significance of the incorporation of these two concepts into the mainstream project evaluation framework. This paper is a conceptual attempt to discuss the topic. Hence, it is a qualitative in nature. The author applies the content analysis method through deep and intense readings of the previous texts and literature related to the topics. The author thoroughly examines and analyses the relevant literature and develop the relationship between maslahah and Shari'ah objectives with the mainstream framework of project evaluation. The paper found that the concept of maslahah and Shari'ah objectives doctrine establish a more detailed order of priorities amongst competing projects, rationalises choices under the light of the Shar'ah and ensure the coherence of the selected project with the Islamic system as a whole. The public and private institutions could establish ranking of priorities for the potential competing projects based on the maslahah and Shariah Objectives analysis of the projects to determine the best solution for resources allocation in an Islamic framework.